Aspects of toxoplasma infection on the reproductive system of experimentally infected rams (ovis aries) - Lopes, Welber Daniel Zanetti [UNESP]; Costa, Alvimar José da [UNESP]; Santana, Luis Fernando [UNESP]; Santos, Ricardo Silva dos [UNESP]; Rossanese, Walter Matheus [UNESP]; Lopes, Wilton Carlos Zanetti [UNESP]; Costa, Gustavo Henrique Nogueira [UNESP]; Sakamoto, Cláudio Alessandro [UNESP]; Santos, Thais Rabelo dos [UNESP] (Hindawi Publishing Corporation, 2009)
Eight reproductive rams with no prior reproductive disease were distributed into three groups of infection with T. gondii: GI, 3 rams, 2.0 x 10(5) P strain oocysts; GII, 3 rams, 1.0 x 10(6) RH strain tachyzoites; GIII, 2 control rams. Clinical parameters were measured and serological evaluations (IIF) were performed. Presence of the parasite in the semen was investigated by PCR and bioassay techniques. The rams presented clinical alterations (hyperthermia and apathy) related to toxoplasmosis in both groups infected with Toxoplasma gondii. All the inoculated rams responded to antigenic stimulus, producing antibodies against T. gondii from postinoculation day 5 onwards. In ovine groups I and II, the greatest titers observed were 1 : 4096 and 1 : 8192, respectively. In semen samples collected from these two groups, the presence of T. gondii was detected by bioassay and PCR. This coccidian was isolated (bioassay and PCR) in tissue pools (testicles, epididymis, seminal vesicle, and prostrate) from two rams infected presenting oocysts and in one presenting tachyzoites.